AFRICAN MUSIC AND ORAL DATA, A catalog of field recordings 1902-1975 by Ruth Stone and Frank Gillis, Indiana University Press, Bloomington and London, 1976, pp. 412. - Coplan, David B. (International Library of African Music, 1980)
pages: 131-132
Keywords: African Music